Do Organizational Innovation and SHRM Practices Improve Organizational Resilience? The Mediating Role of Employee Resilience - Nelson, Alden; Lie, Wynne; Setyawan, Agustinus (Universitas Muhammadiyah Yogyakarta, 2025)
Research aims: This research endeavor seeks to investigate the correlation between Organizational Innovation and Strategic Human Resource Management (SHRM) Practices in relation to Organizational Resilience, with a focus on the mediating influence of Employee Resilience.Design/Methodology/Approach: A quantitative methodological approach, encompassing causal-comparative analysis and partial least squares structural equation modeling, had been utilized to undertake the investigation. The sample was derived from the perspectives of 328 employees of rural banks situated in Batam City.Research findings: The findings show that both Organizational Innovation and Strategic Human Resource Management Practices markedly contribute to the enhancement of Organizational Resilience. Furthermore, Employee Resilience serves as a mediating factor in the relationship between Organizational Innovation and Strategic Human Resource Management Practices and Organizational Resilience, thereby underscoring the significance of cultivating a resilient workforce to attain substantial organizational results.Theoretical Contribution/Originality: This research has the potential to furnish a comprehensive analysis of the mechanisms through which Organizational Resilience may facilitate the navigation of external challenges and pressures that have the capacity to influence business performance and continuity.Research Limitations/Implications: This study centers on variables while neglecting to examine additional potential factors that could impact organizational resilience which may contribute to a more comprehensive understanding of resilience.